Atypical spatiotemporal activation of cerebellar lobules during emotional face processing in adolescents with autism. Issue 7 (2nd February 2021) - Styliadis, Charis; Leung, Rachel; Özcan, Selin; Moulton, Eric A.; Pang, Elizabeth; Taylor, Margot J.; Papadelis, Christos
Abstract: Autism spectrum disorder (ASD) is characterized by social deficits and atypical facial processing of emotional expressions. The underlying neuropathology of these abnormalities is still unclear. Recent studies implicate cerebellum in emotional processing; other studies show cerebellar abnormalities in ASD. Here, we elucidate the spatiotemporal activation of cerebellar lobules in ASD during emotional processing of happy and angry faces in adolescents with ASD and typically developing (TD) controls. Using magnetoencephalography, we calculated dynamic statistical parametric maps across a period of 500 ms after emotional stimuli onset and determined differences between group activity to happy and angry emotions. Following happy face presentation, adolescents with ASD exhibited only left‐hemispheric cerebellar activation in a cluster extending from lobule VI to lobule V (compared to TD controls). Following angry face presentation, adolescents with ASD exhibited only midline cerebellar activation (posterior IX vermis). Our findings indicate an early (125–175 ms) overactivation in cerebellar activity only for happy faces and a later overactivation for both happy (250–450 ms) and angry (250–350 ms) faces in adolescents with ASD. The prioritized hemispheric activity (happy faces) could reflect the promotion of a more flexible and adaptive social behavior, while the latter midline activity (angry faces) may guide conforming behavior. Abstract : The present study demonstrates distinct spatiotemporal patterns of cerebellar activity during happy and angry face processing in adolescents with autism spectrum disorder (ASD). ASD‐related emotional face processing during adolescence relates to a progression of overactivation of both hemispheric and midline cerebellar lobules. Our findings highlight that adolescents with autism spectrum disorder do not integrate cerebellar regions into the processing of emotional facial stimuli in a fashion similar to that of typically developing controls.